Starches : (Taylor & Francis, 2010)
The book provides an up-to-date overview of starch applications in the food, textiles, pharmaceuticals, chemical, agricultural, and plastic industries when used as a substitute for synthetic polymers. Starch nanocomposites properties and starch-based blends biodegradability are also discussed. The book covers the recent advances made in starch characterization using techniques such as atomic force microscopy and nuclear magnetic resonance. It discusses the main modified starches applications and enzymes used on starch industry. It also addresses starch characterization at the granular, macromolecular, and rheological levels.